Prolonged Inhibition of Streptococcus mutans Growth and Biofilm Formation by Sustained Release of Chlorhexidine from Varnish Coated Dental Abutments: An in Vitro Study - Mark Feldman; Walid Shaaban Moustafa Elsayed; Michael Friedman; Irith Gati; Doron Steinberg; Hesham Marei (Hindawi Limited, 2022)
Background. It has been confirmed that bacterial biofilm covering dental implants is the main microbial source causing preimplant infectious and inflammatory diseases. The purpose of this study was to evaluate the antibacterial/antibiofilm effect of chlorhexidine, incorporated into a sustained-release varnish of chlorhexidine (SRV-CHX) coating, on dental abutments. Materials and Methods. Three kinds of dental abutments were used: a high-performance semi-crystalline engineering thermoplastic polyetheretherketone (PEAK) healing abutment, a titanium healing abutment, and a titanium permanent abutment. These abutments were coated with SRV-CHX or SRV-placebo and exposed daily to fresh cultures of Streptococcus mutans. The effect of SRV-CHX on S. mutans growth on agar plates was studied by measuring the zone of inhibition (ZOI) around each tested abutment every day for a period of 36 days. Biofilm formation on the SRV-CHX/placebo-coated abutments was detected using confocal laser scanning microscopy (CLSM) and high-resolution scanning electron microscopy (HR-SEM), energy dispersive X-ray analysis (EDX), and monitored by crystal violet (CV) staining. Results. SRV-CHX-coated abutments 2 and 3 were able to inhibit S. mutans growth for 34 days, while abutment 1 inhibited growth for 32 days. Abutment-associated biofilm formation was notably inhibited by SRV-CHX coating after 13 days of incubation with S. mutans. Finally, the biofilm formed around SRV-CHX-coated abutments was completely inhibited up to 12 days of abutment exposure to S. mutans. Conclusion. Coating of dental abutments with SRV-CHX demonstrated long-term effective inhibition of S. mutans growth and biofilm formation on the abutment surface.